Antioxidant Effect of Natural Table Olives Phenolic Extract Against Oxidative Stress and Membrane Damage in Enterocyte‐Like Cells. Issue 2 (10th January 2017) - Serreli, Gabriele; Incani, Alessandra; Atzeri, Angela; Angioni, Alberto; Campus, Marco; Cauli, Emanuele; Zurru, Roberto; Deiana, Monica
Abstract: The phenolic fraction of a naturally fermented cultivar of table olives, "Tonda di Cagliari, " was investigated for the ability to protect Caco‐2 cells against oxidative stress and membrane damage induced by tert‐butyl hydroperoxyde (TBH). TBH exposure resulted in an alteration of cellular redox status, with an increase in reactive oxygen species (ROS) and a decrease in reduced glutathione (GSH) level. A loss of the epithelial integrity, as indicated by the decrease of the transepithelial electrical resistance value, was also observed over time, together with an intense lipid peroxidation process. The olives phenolic extract significantly counteracted ROS generation and subsequent alteration of monolayer integrity and membrane oxidative damage. The protective action of the extract is likely due to the scavenging ability of its main components, as hydroxytyrosol, oleuropein, and verbascoside among the secoiridoids and derivatives. Since olives phenolic compounds concentrate in the intestinal lumen, they may be a useful tool in the prevention of intestinal disorders related to oxidative damage.